Riesgos laborales y seguridad industrial en la empresa Equatoroses EQR de la provincia de Cotopaxi. Diseño de un manual de seguridRiesgos laborales y seguridad industrial en la empresa Equatoroses EQR de la provincia de Cotopaxi. Diseño de un manual de seguridad industrial para la empresa Equatoroses EQR.ad industrial para la empresa Equatoroses EQR. - Coello Renjifo, Diego Patricio (2012)
The present investigation work has as main objective to develop and to establish appropriate procedures to prevent accidents/incidents in the company EQR, allowing the elimination or minimization of labor risks in the processes of cultivation of roses. This system of prevention of labor risks is guided to mitigate the effects of damages caused by an accident/incident to people, property or atmosphere; preparing this way the necessary measures to eliminate the problems that affect the productivity, the Security and Physical Integrity of the Workers whose problem is framed specifically in the labor Security that is managing in the field and its incidence like such, in the increase of the risk of accidents / incidents and possible occupational illnesses, inside the processes of cultivation of roses. The company EQR for its economic activity possesses a great quantity of inputs classified as dangerous, the same one that you are used in fertilization activities and fumigation of roses that combined with the time of exhibition it is a latent risk in the process of cultivation of roses, for what requires in an urgent way to carry out an evaluation of labor risks allowing us this way to identify the risks classified as moderate, important and intolerable, the same ones that require an immediate performance creating preventive actions and correctivs, either in engineering controls, means trasmisor and for I finish in the workers that allow to be captured in a manual the preventive instructions. Before a serious event that can derive in consequences for the physical integrity of the workers. Therefore for this investigative work I will base myself on the bibliographical revision and field investigation since is supported in what refers to technical words and the application of surveys allowing us this way to solve the opposing problems.